Interactions with native microbial keystone taxa enhance the biocontrol efficiency of Streptomyces - Tianyu Sun; Hongwei Liu; Ningqi Wang; Mingcong Huang; Samiran Banerjee; Alexandre Jousset; Yangchun Xu; Qirong Shen; Shimei Wang; Xiaofang Wang; Zhong Wei (Microbiome)
Abstract Background Streptomyces spp. are known for producing bioactive compounds that suppress phytopathogens. However, previous studies have largely focused on their direct interactions with pathogens and plants, often neglecting their interactions with the broader soil microbiome. In this study, we hypothesized that these interactions are critical for effective pathogen control. We investigated a diverse collection of Streptomyces strains to select those with strong protective capabilities against tomato wilt disease caused by Ralstonia solanacearum. Leveraging a synthetic community (SynCom) established in our lab, alongside multiple in planta and in vitro co-cultivation experiments, as well as transcriptomic and metabolomic analyses, we explored the synergistic inhibitory mechanisms underlying bacterial wilt resistance facilitated by both Streptomyces and the soil microbiome. Results Our findings indicate that direct antagonism by Streptomyces is not sufficient for their biocontrol efficacy. Instead, the efficacy was associated with shifts in the rhizosphere microbiome, particularly the promotion of two native keystone taxa, CSC98 (Stenotrophomonas maltophilia) and CSC13 (Paenibacillus cellulositrophicus). In vitro co-cultivation experiments revealed that CSC98 and CSC13 did not directly inhibit the pathogen. Instead, the metabolite of CSC13 significantly enhanced the inhibition efficiency of Streptomyces R02, a highly effective biocontrol strain in natural soil. Transcriptomic and metabolomic analyses revealed that CSC13’s metabolites induced the production of Erythromycin E in Streptomyces R02, a key compound that directly suppressed R. solanacearum, as demonstrated by our antagonism tests. Conclusions Collectively, our study reveals how beneficial microbes engage with the native soil microbiome to combat pathogens, suggesting the potential of leveraging microbial interactions to enhance biocontrol efficiency. These findings highlight the significance of intricate microbial interactions within the microbiome in regulating plant diseases and provide a theoretical foundation for devising efficacious biocontrol strategies in sustainable agriculture. Video Abstract